Structural Studies of Donor‐Free and Donor‐Solvated Sodium Carboxylates. Issue 16 (22nd March 2021) - Gauld, Richard M.; McLellan, Ross; Kennedy, Alan R.; Carson, Freya J.; Barker, Jim; Reid, Jacqueline; O'Hara, Charles T.; Mulvey, Robert E.
Abstract: Focusing mainly on sodium 2‐ethylhexanoate, this study reveals that the carboxylate exists as a dimer in MeOD solution as evidenced by Diffusion Ordered NMR SpectroscopY (DOSY). Two crystalline varieties with distinct polymeric structures have been synthesised and crystallographically characterised. A mixed 1, 10‐phenanthroline–water solvate [(C5 H10 )(C2 H5 )COONa.(H2 O)[1, 10‐phen]2 ]∞ contains dimeric [Na(OH2 )]2 subunits, which propagate through hydrogen bonds between O atoms of the carboxylate and OH water bonds. Adjacent polymeric chains interdigitate with each other through π−π interactions between 1, 10‐phen rings. Solvent‐free sodium 2‐ethylhexanoate has five‐coordinate cations comprising one bidentate chelating and three monodentate carboxylate oxygen atoms. Here, the packing arrangement is different with the central hydrophilic (NaO2 )∞ core surrounded by a wrapping of disordered alkyl groups. A similar polymeric structure is observed for the crystalline DMSO‐solvated sodium valproate [(C3 H7 )(C4 H8 )COONa.(DMSO)]∞ . This adopts a layered arrangement comprising alternating sodium carboxylate hydrophilic layers and hydrophobic organic bilayers. Abstract : Characterising the Culprits : Industrially important; but also problematic in the operation of diesel engines, long chain sodium carboxylates have been notoriously difficult to crystallographically characterise. Here, successful crystallisation and structural determination of three sodium carboxylates and a sodium‐free variant highlights the structural complexity and diversity in this area.